Experimental investigation of a borehole field by enhanced geothermal response test and numerical analysis of performance of the borehole heat exchangers. (1st May 2015) - Luo, Jin; Rohn, Joachim; Xiang, Wei; Bayer, Manfred; Priess, Anna; Wilkmann, Lucas; Steger, Hagen; Zorn, Roman
Abstract: Thermal conductivity of the ground is generally measured in field by TRT (thermal response test) without considering non-uniformity and the groundwater flow. However, both factors can affect the performance of BHE (borehole heat exchangers) drastically. Hence, analysis of thermal conductivity in layered subsurface with taking into account groundwater flow and its effect on performance of BHE is necessary. This paper analyzes thermal conductivity of a layered subsurface by both EGRT (enhanced geothermal response test) and laboratory measurement. Five different geological strata are investigated in a borehole field within depth of 80 m. In addition, flowmeter tests are implemented to examine the groundwater flow. Experimental results indicate: (1) EGRT fit very well with laboratory measurements in the strata without groundwater flow; (2) under groundwater flow, the EGRT leads to unreasonable outcomes due to convection effects. The effect of groundwater flow on thermal performance of the BHE is further examined numerically. The modeling results show that heat transfer efficiency of the BHE increases by 55% within the aquifer. Therefore, the effects of groundwater on performance of BHE deserve to be considered in order to minimizing the total length of BHE in layered subsurface. Highlights: We measure thermal conductivity of layered ground by EGRT and laboratory tests. EGRT fit very well with laboratory measurement without groundwater flow. The EGRT deviate drastically to the laboratory outcomes under groundwater flow. Heat transfer rate of BHE increases by 55% with groundwater flow.